The Effects of Slope and Frequency of Stem Cutting in the Water to the Vase Life of Cut Orchid Vanda douglas - Ayuta Ratu Balqis, Didik Indradewa, dan Sri Trisnowati (Vegetalika, 2013)
ABSTRACT Orchid is one of the highly prospective ornamental plants. Orchid cultivation is one of the most popular ornamental cultivation. That is because the demand for orchids are relatively stable compared to other plants that tend to follow the trend or fluctuating. One form of massive utilization of orchids is the use as a cut flower. One type of orchid that mostly sold as a cut flower is Vanda douglas. Orchid’s –including Vanda douglas- advantage than other cut flowers are the vase life that tend to be longer. Nonetheless, the effort to maintain even extend the vase life of the flower is still needed. This experiment was conducted to determine the effect of cutting the flower stem with a combination of cutting slope and conditions of the stem and cutting frequency of the stem on vase life of cut orchid Vanda douglas.The experiment was conducted at the Laboratory of Horticulture, Faculty of Agriculture, Gadjah Mada University from July to September 2012. The first phase of the study used a completely randomized design with 2 factors. The first factor was cutting slope consisted of 0, 30 and 45. The second factor was cutting conditions consisted of water cut and air cut. The second phase also used completely randomized design with cutting stem frequency consisted of every day, every 2 days, every 4 days and every 6 days. Presentations of flowers bloom, wilt, fall, respiration, transpiration and visual quality rating of the cut flower were observed every day. Flower’s shrinkage, stomata and relative water content were observed at the beginning and end of the experiment.The results showed there was no interaction between the slope and condition of stem cutting on all parameters of the observations. Cutting stem with a slope of 45 caused longer vase life than the other slopes. Cutting the flower stem in the water also caused a longer vase life than cutting through the air. Flower stem that was cut at intervals of 4 days caused the longest vase life than any other time frequency. Nevertheless, the extent of vase life of cut flowers only extend a day, therefore the benefits for a florist should be reexamined. Key words : Cut orchid, cutting slope, cutting conditions, cutting frequency, vase life